Prevalence of infectious bovine rhinotracheitis in repeat breeder cows - Risvanli, A.; Alparslan, S. (Wiley-Blackwell, 2012)
[Abstract Not Available]
16th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- AUG 29-SEP 01, 2012 -- Univ Coll Dublin (UCD), Befield Campus, UCD Vet Sci Ctr, Dublin, IRELAND